MENILIK PERSPEKTIF POSITIF NON-MUSLIM TERHADAP URGENSI BAHASA ARAB SEBAGAI UPAYA MENAMPIK STIGMA SAKRAL DALAM MASYARAKAT UMUM DI INDONESIA - Miftahul Akhera Idris; Yayan Nurbayan; Rinaldi Supriadi; Dandi Donovan Dyas Saputra (STIT Sunan Giri Bima, 2023)
Arabic, which is closely known as part of Islam because it was chosen directly by God as the language of the Qur'an and Hadith, now seems to be an exclusive language to learn. Since long ago, the views of the Indonesian people, especially non-Muslims, towards Arabic were only limited to religious languages without seeing the urgency of the Arabic language itself. Therefore, this study wants to reveal the positive views of non-Muslims towards Arabic because researchers believe that not all non-Muslim Indonesians think that way. This is done to open the views of the sacredness of the Indonesian people towards Arabic. This study uses a mixed methods approach between qualitative and quantitative. The instrument used was the Forum Group Discussion (FGD) with each representative from a non-Islamic religion in Indonesia and as supporting data, the researcher conducted reference searches in journal articles and the like. As an introduction, the researcher reveals that there is an alignment or de-sacralization of Arabic objects. Then the researcher found the influence of Arabic on non-Muslim objects of worship and its influence on the international scene. In addition, the practical and pragmatic orientation of non-Muslims towards learning Arabic and the opportunity to make it part of the National curriculum can also have an impact on the process of open-mindedness in society, which until now still consecrates the Arabic language with parallelism or de-sacralization of Arabic objects.